Correlation between Strawberry (Fragaria ananassa Duch.) Productivity and Photosynthesis-related Parameters under Various Growth Conditions - Hyo Gil Choi (Frontiers in Plant Science, 2016)
In the present study, we investigated changes in chlorophyll fluorescence, photosynthetic parameters and fruit yields, as well as fruit phytochemical accumulation of strawberry (Fragaria ananassa Duch.) that had been cultivated in a greenhouse under different combinations of light intensity and temperature. In plants grown with low light (LL) photosystem II chlorophyll fluorescence was found to increase as compared with those grown under high light (HL). When strawberry plants were grown with temperature higher than 5◦C in addition to LL, they showed decrease in non-photochemical quenching (NPQ), photochemical quenching (qP), as well as chlorophyll fluorescence decrease ratio (RFd) when compared with other combinations of light and temperature. Moreover, fruit yield of strawberry was closely correlated with chlorophyll fluorescence-related parameters such as NPQ, qP, and RFd, but not with the maximum efficiency of PS II (Fv/Fm). Although plant groups grown under different combinations of light and temperature showed almost comparable levels of photosynthesis rates (Pr) when irradiated with low-intensity light, they displayed clear differences when measured with higher irradiances. Plants grown under HL with temperature above 10◦C showed the highest Pr, in contrast to the plants grown under LL with temperature above 5◦C. When the stomatal conductance and the transpiration rate were measured, plants of each treatment showed clear differences even when analyzed with lower irradiances. We also found that fruit production during winter season was more strongly influenced by growth temperature than light intensity. We suggest that fruit productivity of strawberry is closely associated with chlorophyll fluorescence and photosynthesis-related parameters during cultivation under different regimes of temperature and light.